Development of Interactive Learning Model Teams Games Tournament Assisted Media Rolling Ball Game in Elementary School - Tukina; Baderiah; Firman (Didaktika: Jurnal Kependidikan, 2022)
This research aims to improve students' morale and learning outcomes by using an interactive learning model of teams games tournaments assisted by rolling ball game media. This type of research uses Research and Development (R&D) development research. The study used the Dick & Carey development model, consisting of 10 stages, but researchers only used five. The analysis stage is carried out to analyze learning needs consisting of analysis of learning objectives, analysis of characteristics of learners, developing research instruments, developing learning strategies, and developing teaching materials. Three validators further validate the model that has been created in the course: validator design, language validator, and material validator. Validation results are then analyzed to find out the validity of the product that has been stored and is very valid value with a percentage of 85.7%. The results are evidenced by the value of the material expert 80%, the value of the linguist 90%, and the design expert 87%. From the results of practicality data that have been obtained, it is known that 7 points score researchers there are six good with a percentage of 75%, and there is an excellent 1 with a percentage of 100%. Therefore, the total is very practical value with a percentage of 90%. From this research, it can be concluded that this learning model can improve learners' spirit and learning outcomes.